Architecture and Self-Assembly of Clostridium sporogenes and Clostridium botulinum Spore Surfaces Illustrate a General Protective Strategy across Spore Formers - Thamarai K. Janganan (American Society for Microbiology, 2020)
ABSTRACT Spores, the infectious agents of many Firmicutes, are remarkably resilient cell forms. Even distant relatives can have similar spore architectures although some display unique features; they all incorporate protective proteinaceous envelopes. We previously found that Bacillus spores can achieve these protective properties through extensive disulfide cross-linking of self-assembled arrays of cysteine-rich proteins. We predicted that this could be a mechanism employed by spore formers in general, even those from other genera. Here, we tested this by revealing in nanometer detail how the outer envelope (exosporium) in Clostridium sporogenes (surrogate for C. botulinum group I), and in other clostridial relatives, forms a hexagonally symmetric semipermeable array. A cysteine-rich protein, CsxA, when expressed in Escherichia coli, self-assembles into a highly thermally stable structure identical to that of the native exosporium. Like the exosporium, CsxA arrays require harsh “reducing” conditions for disassembly. We conclude that in vivo, CsxA self-organizes into a highly resilient, disulfide cross-linked array decorated with additional protein appendages enveloping the forespore. This pattern is remarkably similar to that in Bacillus spores, despite a lack of protein homology. In both cases, intracellular disulfide formation is favored by the high lattice symmetry. We have identified cysteine-rich proteins in many distantly related spore formers and propose that they may adopt a similar strategy for intracellular assembly of robust protective structures. IMPORTANCE Bacteria such as those causing botulism and anthrax survive harsh conditions and spread disease as spores. Distantly related species have similar spore architectures with protective proteinaceous layers aiding adhesion and targeting. The structures that confer these common properties are largely unstudied, and the proteins involved can be very dissimilar in sequence. We identify CsxA as a cysteine-rich protein that self-assembles in a two-dimensional lattice enveloping the spores of several Clostridium species. We show that apparently unrelated cysteine-rich proteins from very different species can self-assemble to form remarkably similar and robust structures. We propose that diverse cysteine-rich proteins identified in the genomes of a broad range of spore formers may adopt a similar strategy for assembly.